Advancing the Shift-of-Strategy approach: Shifting suspects' strategies in extended interviews - Nyström, Lina; Luke, Timothy J; Granhag, Pär Anders; Dönmez, Aziz-Kaan; Ekelund, Malin; Stern, Pär D (Law and human behavior, 2024)
Interviewers often face the challenge of obtaining information from suspects who are willing to speak but are motivated to conceal incriminating information. The Shift-of-Strategy (SoS) approach is an interviewing technique designed to obtain new information from such suspects. This study provides a robust empirical test of the SoS approach using more complex crime events and longer interviews than previously tested as well as testing a new variation of the approach (SoS-Reinforcement) that included a strategic summary of the suspect's statement. We compared this new variation with a standard version of the approach (SoS-Standard) and an interviewing approach that involved no confrontation of discrepancies in the suspects' statements (Direct). We predicted that the two SoS versions would outperform the Direct condition in terms of participants' disclosure of previously unknown information. We also predicted that SoS-Reinforcement would outperform SoS-Standard. Finally, we expected that participants in the SoS conditions would not assess the interview or the interviewer more poorly than participants in Direct. A total of 300 participants completed an online mock crime procedure, and they were subsequently interviewed with one of the three interviewing techniques. Following the interview, participants provided assessments of their experiences being interviewed. Participants in both SoS-Standard (d = 0.49, 95% confidence interval [CI: 0.21, 0.78]) and SoS-Reinforcement (d = 0.59, 95% CI [0.30, 0.87]) disclosed more previously unknown information than participants in the Direct condition, but SoS-Reinforcement did not outperform SoS-Standard (d = 0.08, 95% CI [-0.20, 0.36]). Participants in SoS-Reinforcement assessed their experience more negatively than those in Direct. No such differences were observed in the remaining two-way comparisons. The study provides support for the effectiveness of eliciting new information through the SoS approach and illuminates possible experiential downsides with being subjected to the SoS-Reinforcement approach. (PsycInfo Database Record (c) 2024 APA, all rights reserved).